2013
DOI: 10.1371/journal.pone.0077355
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Prunella vulgaris on the Mice Immune Function

Abstract: The present study was designed to evaluate the effects of Prunella Vulgaris (P. vulgaris) on the immune function in mice. The mice were randomly divided into one control group and three treatment groups of 10 mice each. The control group received pure water and the treatment groups received P. vulgaris extract at concentrations of 0.15, 0.30 and 0.90 g/kg BW orally for 30 days, respectively. Changes in cell immune function, non-specific immunity and humoral immunity function were evaluated. Active lymphocytes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 10 publications
0
22
0
Order By: Relevance
“…vulgaris has been proven to have many biological functions including antiproliferation of cancers, immune modulation, cytoprotection, and anti-oxidative response (Feng et al, 2010, Huang et al, 2013, Hwang et al, 2013. However, its function within the brain remains unclear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…vulgaris has been proven to have many biological functions including antiproliferation of cancers, immune modulation, cytoprotection, and anti-oxidative response (Feng et al, 2010, Huang et al, 2013, Hwang et al, 2013. However, its function within the brain remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Reports have demonstrated that Prunella vulgaris has many biological functions including anti-oxidant, anti-cancer, anti-inflammation, and cytoprotection against injury or immune stimulation (Harput et al, 2006, Huang et al, 2013, Hwang et al, 2013.…”
Section: Introductionmentioning
confidence: 99%
“…The suspension of splenic cells was prepared by methods as described in the study by Ladics. 31 Further details of the method are described in the studies by Ladics 31 and Huang et al 32 The results were expressed as plaque-forming cells (PFC) number/10 6 cells.…”
Section: Determination Of Immune Parameters Measuring the Primary Immmentioning
confidence: 99%
“…On the last day (t=28 d), blood was collected from the angular vein before the mice were sacrificed. Further details of the method are described in the studies by Huang et al 32 and Costabile. 33 The OD was measured at 540 nm.…”
Section: Measurement Of Serum Hemolysin Levelmentioning
confidence: 99%
See 1 more Smart Citation